KONSEP BLUE ECONOMY TERHADAP PEMBANGUNAN EKONOMI DI INDONESIA - Nota Morra Banu (Ekonis: Jurnal Ekonomi dan Bisnis, 2020)
Abstract: Indonesia is one of the countries with the longest coastline in the world, where its use only around 59%, therefore the potential of sea is very feasible to be developed and studied in depth. Blue economic itself is closely related to Minapolitan, an inter firm linkage concept. The concept will be able to become a new supporting sector in the economy and can increase the productivity of marine and fisheries in Indonesia. Keywords : blue economy, minapolitan, productivity